Integral-derivative (I-D) and modulation-index-curve prediction control techniques for three-phase AC-DC buck-type converter with simplified voltage-based SPWM /Azrita Alias - Azrita, Alias (2015)
This thesis presents the design of a three-phase AC-DC buck-type converter with bidirectional capability using simplified voltage-based sinusoidal pulse-width-modulation (SPWM) switching technique. With its four diodes connected to the switch enable bidirectional power flow in each switch. The proposed topology is an extension of the conventional 6-switch three-phase AC-DC buck-type converter whereas the proposed switching technique is a simplification of conventional modified SPWM technique. It uses one reference signals (0-60° sine wave) and one type carrier signal, instead of two reference signals and two types of carrier signals to generate PWM signals. The proposed circuit configuration produces sinusoidal AC current with low THD at near unity power factor using simplified voltage-based SPWM. Voltage feedback control allows high dynamic performance of the DC output voltage in the step-changing of reference and disturbance. Two digital feedback voltage controls, Integral-Derivative (I-D) and modulation-index-curve prediction techniques, are suggested to equalize the output voltage to the reference voltage with high dynamic performance and simpler implementation. The algorithm of the modulation-index-curve prediction technique is obtained through I-D control model by determining closed-loop dominant poles. By assuming zero system loss, a small steady-state error is still present (absent in the I-D controller). Modulation-index-curve-prediction technique is still advantageous because it reduces dependence on feedback-sensor reading and simplifies the I-D algorithms. The converter’s validity, PWM switching strategy, and feedback control strategy have been verified by simulation using MATLAB/Simulink. The hardware prototype has been implemented in a TMS320F28335 Digital Signal Processor (DSP) and the results are validated.